Uma hipótese de funcionamento psicomotor para a clínica de intervenção precoce - Peruzzolo, Dani Laura (2016)
This thesis aimed to build and analyze the effectiveness of a Psychomotor Operating Hypothesis as a strategy for treatment in early intervention term and preterm babies at risk for the development and / or psychological risk. As a secondary objective, gathered theoretical frameworks that integrate a Psychomotor Working Hypothesis, from studies on child development, structure aspects and instruments, the main psychomotor conceptual elements: Schema (EC) and body image (IC) and the clinical intervention early. The thesis has qualitative character, longitudinal, clinical quasi-experimental. Is part of a study evaluating babies in order to identify whether there are differences in the results of PRÉAUT protocols, Child Development Risk Indicators (IRDls) and Denver II, between preterm and term. The thesis of the strategy was research from multiple case study. The sample was for convenience, being a baby born preterm and full term, identified with psychological risk and / or delay in development in the study mentioned above. The babies were treated in early intervention by an occupational therapist, and gave up from a psychomotor working hypothesis for three and five months, respectively. The visits occur once a week, and were filmed and reported in a field diary. The footage was used to identify scenes to contribute in the discussion on the effectiveness or otherwise of treatment in early intervention based on the Psychomotor Working Hypothesis. The results were obtained by comparing the stated objectives and effects of treatment, identifying the approach strategies. The two cases confirm that psychomotor irregularity presented as delay problem in the psychomotor development in both with a psychomotor agitation in one case, that can be treated from a psychomotor working hypothesis, considering the uniqueness of the interpretation of symptoms as a announcement Baby on themselves and on the other, guided by family year in which the baby is encouraged to do / be. Confirmed the sensitivity of PRÉAUT, IRDls and protocols for delay detection risk in the development and / or psychological. Results reinforced the thesis that a psychomotor working hypothesis is an important procedure for evaluation in the clinic with baby. They emphasize the importance of the interpretation of the effect of the construction of IC on the baby EC in a dialectical relationship with their parents. HF is interpreted in light of the psychoanalytic concepts of maternal and paternal role to ensure the desired places subject to assumption and castrated, from the place of the parents of the sinthome. The EC is taken as the motor and cognitive functioning announcing the psychic place where the IC is being prepared, breaking with the idea of behavioral treatment for babies. From the perspective of an occupational therapist, clinical early intervention built through psychomotor clinic of contributions taken as a do / be, can be used to treat babies who have developmental delay with symptoms of motor skills, cognitive and psychological that They should be interpreted in light of a psychomotor function hypothesis.